A One Health approach to the prevention, control, and management of leptospirosis: a scoping review - Khristine L. Sandoval; Kristel Joy S. Cada; Rodel Victor D. Dimasin; Ryan V. Labana (Discover Public Health)
Abstract Leptospirosis is a significant zoonotic disease that poses a global public health challenge, particularly in warm, humid regions. The aim of this review paper is to critically synthesize existing literature on interventions for leptospirosis at the interfaces of humans, animals, and the environment. It also emphasizes the importance of interdisciplinary collaboration and integrated approaches to effectively address the complex challenges posed by this infectious disease. The authors conducted a systematic scoping review following the PRISMA-ScR guidelines and analyzed 344 studies that met the inclusion criteria. The paper highlights advancements in diagnostic techniques, treatment, and vaccine development. It also emphasizes the significance of health governance frameworks that support risk communication, surveillance, policy development, and community engagement. Various health interventions related to each interface are discussed, and the paper concludes with a discussion regarding One Health approach to interventions, which highlights the key targets, including pathogen characteristics and transmission. This paper proposes a framework for leptospirosis interventions across the human-animal-environment interfaces, which may serve as a guide for policymakers and scientists in understanding the gaps and less explored aspects of intervening in leptospirosis.